2020
DOI: 10.1016/j.jpeds.2019.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Are Children with a History of Asthma More Likely to Have Severe Anaphylactic Reactions? A Retrospective Cohort Study

Abstract: Objective To assess whether a history of asthma was associated with anaphylaxis severity in children hospitalized for anaphylaxis. Study design Retrospective cohort study of children £21 years old hospitalized for anaphylaxis from 2009 to 2016. The primary outcome was severe anaphylactic reactions defined by examination findings (stridor, respiratory distress, or hypotension) or administered therapies (³2 dose of intramuscular epinephrine, continuous albuterol, vasopressors, or positive pressure ventilation). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Wheeze is the characteristic finding in anaphylaxis, but stridor can be found when upper airway is affected and though stridor is less common, it is much more dangerous. A recent study found stridor in only 6.3% of cases of anaphylaxis [23].…”
Section: Discussionmentioning
confidence: 91%
“…Wheeze is the characteristic finding in anaphylaxis, but stridor can be found when upper airway is affected and though stridor is less common, it is much more dangerous. A recent study found stridor in only 6.3% of cases of anaphylaxis [23].…”
Section: Discussionmentioning
confidence: 91%
“…In support of their conclusions, the authors cite a study evaluating anaphylactic reactions from peanuts and tree nuts in an outpatient allergy center. 1 In contrast to our report, this study includes limited allergens and may represent a more severe cohort of patients with a greater predilection for asthma and/or severe anaphylaxis based on their referral to an allergy center. Thus, it is difficult to compare their findings with our own, or generalize them to the care of children presenting to emergency departments (EDs) with anaphylaxis.…”
Section: Replymentioning
confidence: 83%
“…We have read with interest the report by Dribin et al investigating the association between history of asthma and anaphylaxis severity in children. 1 The authors concluded that children hospitalized for anaphylaxis with a medical history of asthma were not more likely to have severe anaphylactic reactions compared with children without asthma. However, we noticed that asthma control status at the time of anaphylaxis was not determined in the study.…”
Section: Replymentioning
confidence: 98%
See 1 more Smart Citation
“…Nine studies exclusively focused on pediatric populations, three on adult populations, while the others included all ages. Three pairs of studies [18][19][20][21][22][23] used the same patient sample and four studies [9,[24][25][26] contained some patient overlap, but the extent was difficult to determine.…”
Section: Study Characteristicsmentioning
confidence: 99%